Light Verb Constructions in Italian: A Corpus-based Analysis of 15th-17th-century Texts - Ganfi, Vittorio (Status Quaestionis, 2023)
This paper aims at analysing the structural and functional features of Light Verb Constructions in Italian. In particular, the investigation is devoted to the analysis of texts written between 1376 and 1691, extracted from the MIDIA corpus.